2009
DOI: 10.3354/meps07767
|View full text |Cite
|
Sign up to set email alerts
|

Chemical defense of a soft-sediment dwelling phoronid against local epibenthic predators

Abstract: Chemical defenses are thought to be infrequent in most soft-sediment systems because organisms that live beneath the sediment rely more on avoidance or escape to reduce predation. However, selection for chemical deterrence might be strong among soft-sediment organisms that are sessile and expose at least part of their body above the surface. The phoronid Phoronopsis viridis is a tube-dwelling lophophorate that reaches high densities (26 500 m -2 ) on tidal flats in small bays in California, USA. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Unpalatability due to chemical deterrents, especially in the anterior section, was found in the phoronid Phoronopsis viridis (Larson & Stachowicz, 2009), which may explain the avoidance of the related phoronid species Phoronis spp. The present results further indicate that effective defences against predators may allow species to reach high densities in the field.…”
Section: P R E Y S E L E C T I O N a N D P R E Y Ava I L A B I L I T mentioning
confidence: 99%
“…Unpalatability due to chemical deterrents, especially in the anterior section, was found in the phoronid Phoronopsis viridis (Larson & Stachowicz, 2009), which may explain the avoidance of the related phoronid species Phoronis spp. The present results further indicate that effective defences against predators may allow species to reach high densities in the field.…”
Section: P R E Y S E L E C T I O N a N D P R E Y Ava I L A B I L I T mentioning
confidence: 99%
“…The phoronid Phoronopsis viridis was studied for its potential chemical defenses. 241 Potential consumers including two fish species, Embiotoca lateralis and Scopaenichthys marmoratus, and three crab species, Hemigrapsus oregonensis, Carcinus maenas and Cancer antennarius, were used to test whether P. viridis deterred feeding. All of the assay organisms ate less of the whole phoronid than the control food except for the crab Cancer antennarius.…”
Section: Other Invertebratesmentioning
confidence: 99%
“…A chemical defence is also sug− gested for the Ordovician-Devonian orthides by Daley (2008). Recent discovery of chemical defense against epi− benthic predators in phoronids (Larson and Stachowicz 2009) may shift the time of acquiring unpalatability by brachiopods (and phoronids) even further back in time, i.e., to the earliest Cambrian, if we accept the hypothesis of inher− iting of unpalatability from their common ancestor.…”
Section: Shell Damagementioning
confidence: 99%
“…As an explanation for abandoning of half−crushed shell of Cyrtiorina sp., Baliński (1993) suggested that the brachiopod developed a skill to emit a repellent. This kind of chemical defence is well known in extant articulate brachiopods (Thayer 1985;Thayer and Allmon 1991), pleurotomarioidean gastropods (Harasewych 2002), and phoronids (Larson and Stachowicz 2009). Recent experiments of Mahon et al (2003) on palatability of soft tis− sue of terebratulid Liothyrella uva (Broderip, 1833) from Antarctica show that the brachiopod is unpalatable to the sympatric macropredators, such as omnivorous sea stars and epibenthic fish.…”
Section: Shell Damagementioning
confidence: 99%